Estudo piloto: avaliação dos efeitos de óleos vegetais na atividade da enzima butirilcolinesterase in vitro - Souza, Leticia de (2022)
Cholinergic neurons are related to important neurological functions that are impaired in cases of deficiency in the secretion of the neurotransmitter acetylcholine (ACh), one of the first neurotransmitters discovered and widespread in the Central Nervous System (CNS). The action of ACh is interrupted when it is hydrolyzed by the enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), present in the synaptic cleft. Thus, the aim of this pilot study was to analyze the inhibition caused by chia, golden linseed, olive oil, sunflower oil and cannabis oil on the in vitro enzymatic activity of BuChE. The evaluation was conducted by the spectrophotometric method of Ellman et al. (1961), with some adaptations. Concentrations of 0.00025 were used; 0.0025; 0.025 and 0.25 µg.L-1 for each oil. The results obtained showed that there was inhibition of BuChE activity for all oils and at all concentrations, with chia and sunflower oils being the ones that most effectively inhibited BuChE activity. From a survey of information on the composition of the oils in relation to the profile in fatty acids, it was observed that these two oils are more abundant in C18:0, C20:4, C18:3n3 and C22:0. Therefore, the study suggests that these fatty acids should be tested for specific inhibitory capacity, in order to assess the possibility of being used as active compounds in the prevention, or as adjuvants in the treatment of AD.